From Sacred to the Possibility of Re-visioning: Arabic Simplification Proposals as Educational Typefaces in Learning Books. - Dhawi, Fahad (2023)
There are special typefaces used for persons with dyslexia, created to learn Katakana, or help children learn to read and write in English. In the process of preliminary research for this paper, no inclusive academic studies were found that have been conducted on the subject of ‘educational typefaces’ for visual Arabic learning or pre-made Arabic typefaces that could meet most of the learning requirements for the adult beginner level. It is acknowledged that while ‘regular’ typefaces cannot fully simplify the learning content or provide appealing learning material with a variety of engaging activities and creative and challenging exercises, they can still help make learning significantly easier in certain parts of the learning unit. Therefore, there is a need for typefaces that can communicate educationally and culturally to a specific audience – basic Arabic learners in the beginner level.